N-cadherin promoter polymorphisms and risk of osteoarthritis - Ruedel, Anke; Stark, Klaus; Kaufmann, Simone; Bauer, Richard; Reinders, Joerg; Rovensky, Jozef; Blazickova, Stanislava; Oefner, Peter J.; Bosserhoff, Anja K. (The FASEB Journal, 2014)
Osteoarthritis (OA) is the most common form of arthritis. It is characterized by cartilage destruction and bone remodeling, mediated in part by synovial fibroblasts (SFs). Given the functional significance of cadherins in these cells, we aimed at determining the role of genetic variants of N-cadherin (CDH2) in OA of the knee and hip. Six single-nucleotide polymorphisms in the genomic region of the CDH2 gene were genotyped in 312 patients with OA and 259 healthy control subjects. Gene expression of CDH2 was analyzed by qRT-PCR. Liquid chromatography-mass spectrometry was used to identify a transcription factor isolated by DNA pulldown. Its potential for binding to gene variants was examined by electrophoretic mobility shift assay, enzyme-linked immunosorbent assay, and chromatin immunoprecipitation. Genetic analysis identified a polymorphism located in the CDH2 promoter region to be associated with risk of OA. The minor allele of rs11564299 had a protective effect against OA. Compared to carriers of the major allele, carriers of the minor allele of rs11564299 displayed increased Ncadherin levels in SFs. Based on in silico analysis, the minor allele was predicted to generate a novel transcription factor binding site, Direct-binding assays and mass spectrometric analysis identified hnRNP K as binding selectively to the minor allele. In summary, a CDH2 promoter polymorphism influences the risk of OA, and hnRNP K was found to be involved in the regulation of elevated N-cadherin expression in patients with OA carrying the minor allele of rs11564299. © FASEB.
CRIS-Team Scopus Importer:2022-08-05
Keywords: CDH2; Genetic association study; HnRNP K; Rs11564299